The mission of university medical journals - Palacios Gómez, Mauricio (2019)
Scientific journals were promoted in the 20th century by scientific societies in Europe and North America, which were organized into large publishing houses with headquarters in Holland, the USA and the United Kingdom, mainly. In Latin America, the development of scientific journals has been supported by universities to a greater extent than by scientific societies or research institutions. Of 98 Peruvian scientific journals in the health area registered in Latindex, 42% are published by universities, while 38.7% are supported by scientific associations, 10.2% by hospitals and clinics and 5% by governmental institutions other than universities and hospitals. Translated with www.DeepL.com/Translator (free version)